0163 Improving Non-technical Skills And Group Dynamics In Obstetric And Gynaecology (obgn) Theatres. (1st November 2014) - Davis, Mike; Gupta, Sujata; Keating, Patrick; Gale, Alison; Pimblett, Mark; Dickinson, Mike; Hanson, Jacky
Abstract : Background/context: Awareness of some challenges to good non technical skills (NTS) practices in OBGN theatre have emerged and staff have recognised the need for some challenges to an emerging, negative culture. Methodology: A mixed group of theatre staff attended a simulation session and engaged in pre and post experience focus group discussions designed to elicit dominant concerns. Among other outcomes (see below) was a need to gain greater insight into the nature of the theatre experience from multiple perspectives and as this proposal is being written, the team is exploring possibilities of video recording real theatre experiences and analysing the outcomes using a variety of approaches, including coding behaviours using the matrix marking system developed on iCoda software (Sportstec) at Lancashire Simulation Centre, LTHTR and "think aloud protocols" (Fonteyn and Fisher 1995). Insights gained from this will inform the design of future simulations where learning needs will be addressed. Results or outcomes: The outcomes from the first round of focus group discussions and their related simulations included an emphasis on role and responsibilties; the challenge of variable team membership; leadership; communication and situation awareness. Further outcomes will be closely monitored during the months between submission and presentation. Potential impact: The desired outcome is improved NTS and group dynamics in OBGN theatre and the project team will monitor this through ongoing observation and other data collection methods. Results will have an impact on other theatre activity and will provide the basis of a curriculum design template to address NTS. References: I Coda - sportstec.com/?s=i+coda Fonteyn M, Fisher A. Use of think aloud method to study nurses' reasoning and decision making in clinical practice sessions. Journal of Neuroscience Nursing 1995;27(2):124–128